培育文化安全的護理能力. - TSAO, Ying (Journal of Nursing, 2026)
Cultural safety extends beyond physical protection to encompass moral considerations and the relational dimensions of care. The determination of whether healthcare is "safe" rests with patients rather than healthcare professionals, and only when patients feel respected, free from denigration, and assured their rights are upheld can care be considered culturally safe. Accordingly, healthcare education must cultivate respect in students for cultural diversity and prepare them to deliver equitable and culturally safe clinical care. In this article, a deconstructive perspective is used to examine the potential of using cultural safety as a framework for addressing health inequities. In practice, cultural safety represents a developmental process progressing from cultural awareness to cultural sensitivity and, ultimately, cultural competence. The cultural teaching capacity of educators may be strengthened through the three interrelated domains of foundational competence, facilitation skills, and curriculum design. Together, these can foster inclusive learning environments and support the development in students of culturally safe nursing practices, which are essential to enhancing quality of care and patient health and well-being.